2020
DOI: 10.1016/j.immuni.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Type 2 cDCs Acquire Features of cDC1s and Macrophages to Orchestrate Immunity to Respiratory Virus Infection

Abstract: Highlights d Type I interferon drives differentiation of inf-cDC2s that closely resemble MCs d Inf-cDC2s prime CD4 + and CD8 + T cells, whereas MCs lack APC function d Inf-cDC2s internalize antibody-complexed antigen via Fc receptors d IRF8 controls maturation gene module in inf-cDC2s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
369
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(393 citation statements)
references
References 107 publications
(169 reference statements)
22
369
0
2
Order By: Relevance
“…Recently, Bosteels et al have shown that in the mouse lung CD26 + CD172 + DC2s in response to type I interferon can up-regulate IRF8 and CD64 and acquire features of both DC1s and monocytes (91). This suggests that there is further complexity of dendritic cells in inflammation, and it stresses the necessity to carefully delineate DC subsets in disease settings, where such inflammatory DC2s increase.…”
Section: Dc2 Subsets In the Mouse In Lungmentioning
confidence: 99%
“…Recently, Bosteels et al have shown that in the mouse lung CD26 + CD172 + DC2s in response to type I interferon can up-regulate IRF8 and CD64 and acquire features of both DC1s and monocytes (91). This suggests that there is further complexity of dendritic cells in inflammation, and it stresses the necessity to carefully delineate DC subsets in disease settings, where such inflammatory DC2s increase.…”
Section: Dc2 Subsets In the Mouse In Lungmentioning
confidence: 99%
“…67 Intriguingly, inf-cDC2 can acquire cDC1 characteristics in a type-I-IFN-dependent manner and become capable of optimally priming CD4 + and CD8 + T cells. 67 The infected lung also contains moDC, which are non-migratory and are poor activators of CD4 + or CD8 + T cells, compared with cDC. 67 Additionally, lung pDC can produce large amounts of type-I-IFN in response to infection with pneumonia virus of mice, inducing a proinflammatory antiviral response.…”
Section: Myeloid Apc In Cbt-sensitive Carcinomasmentioning
confidence: 99%
“…67 The infected lung also contains moDC, which are non-migratory and are poor activators of CD4 + or CD8 + T cells, compared with cDC. 67 Additionally, lung pDC can produce large amounts of type-I-IFN in response to infection with pneumonia virus of mice, inducing a proinflammatory antiviral response. 68 Although the immune-stimulatory potential of lung DC can have protective effects in cancer, the lung TME inhibits their antitumor functions (figure 2), and efforts are underway to test the efficacy of combining a DC-based vaccine with CBT.…”
Section: Myeloid Apc In Cbt-sensitive Carcinomasmentioning
confidence: 99%
“…In vitro differentiated DCs from monocytes (MoDCs) are a broadly accepted model, nevertheless, it has been reported that they functionality could be affected by the treatments used in order to differentiate them (9,(19)(20)(21). Moreover, MoDC are different cells from conventional DC (cDCs) (22) that differentiate in peripheral tissues only in inflammatory conditions, and they do not migrate in the lymph or do it weakly (23) while ALDC are mainly cDC. Charleston and collaborators (9) have developed a technique to cannulate bovine afferent lymphatic vessels, allowing collecting of large volumes of lymph containing afferent lymph dendritic cells (ALDCs).…”
Section: Discussionmentioning
confidence: 99%